Are caregiving appraisal and relationship quality key mediators in informal caregiving burnout? A structural equation modelling study in Belgium and France. (16th December 2021) - Gérain, Pierre; Zech, Emmanuelle
Abstract: Informal caregivers are key players in maintaining chronically ill patients at home but often experience negative consequences such as informal caregiver burnout. The processes by which determinants related to informal care and their personal and social resources affect the caregiver's risk of burnout remains little investigated. Recent theoretical works have suggested that two mediators could play an important role in understanding how these risks and resources influence informal caregiver burnout: by deteriorating how they view their role (caregiving appraisal) and by weakening the relationship with the care‐recipient (relationship quality). The present study aimed at exploring the impact of the care‐recipient's dependency (WHODAS), the caregiver's emotional intelligence (TEIQue‐SF), and loneliness (UCLALS) on informal caregiver burnout (MBI‐ICg). This association was explored both directly and through the mediation of caregiving appraisal (measured by subjective burden, ZBI) and relationship quality. To do so, a sample of 444 French‐speaking informal caregivers completed online questionnaires from November 2017 to August 2018. Structural equation modelling (SEM) was performed to test the mediation model. As a result, the caregiving appraisal appears as a key mediator between determinants and informal caregiver burnout, whereas the relationship quality had a lower predictive value. Among the determinants, emotional intelligence was the strongest protective factor and the care‐recipient's dependency was the strongest risk factor. But beyond this association, the perception informal caregivers have of their role (their caregiving appraisal) is a key mediator between these determinants and informal caregiver burnout, which emphasizes the importance of subjectivity in building risk and protective profiles.